PELATIHAN MENULIS SEBAGAI UPAYA MENINGKATKAN TINGKAT LITERASI MASYARAKAT - Nurfaizah; Nandang Hermanto; Fathuzaen Fathuzaen; Agung Tri Wibowo; Hasri Akbar Awal Rozaq (Politeknik Negeri Sriwijaya, 2022)
Increasing the habit of reading and writing is used as one of the keys to the advancement of a civilization in a country. This is one of the reasons for the government to seek various forms of policies to increase literacy in reading and writing for all Indonesian people. Efforts to improve reading and writing should also be encouraged by the driving parties, both education and the general public. One of the activities that can be done is by holding writing trainings for the community because by writing, we are indirectly forced to read a lot of references. This service is carried out with the aim of increasing public literacy through short story writing seminars. The short story writing training was attended by 166 participants from various provinces in Indonesia and from the results of the questionnaire given to the participants, a very good assessment was obtained from the training participants.